Analysis of the Influence of Tourist Attractions, Memorable Experiences, and Visitor Engagement on Tourists Visiting Decisions at Orangutan Haven - Elveria Melda Sinaga; Erwansyah Erwansyah; Hidayati Purnama Lubis (Utan Kayu Publishing, 2025)
This study aimed to analyze the influence of tourist attractions, memorable experiences, and visitor engagement on visiting decisions at Orangutan Haven. The research employed a quantitative approach with an associative method, which served to identify the relationship between independent and dependent variables. The study was conducted in 2025. The research population consisted of 531 visitors, of whom 84 were selected as the sample. The sampling technique used was purposive sampling. Primary data were collected through questionnaires distributed to respondents and were then analyzed using SPSS version 24 with multiple linear regression analysis. The results showed that, partially, tourist attractions, memorable experiences, and visitor engagement had a positive and significant influence on tourists’ visiting decisions at Orangutan Haven. Simultaneously, tourist attractions, memorable experiences, and visitor engagement also demonstrated a positive and significant influence on visiting decisions, indicating that improvements in these three variables could enhance visitors’ decisions to visit. Among the three variables, visitor engagement was the most dominant factor influencing visiting decisions. A total of 86.1% of the variation in visiting decisions could be explained by tourist attractions, memorable experiences, and visitor engagement, with a very strong relationship indicated by a correlation coefficient (R) value of 0.930